Characteristics of patients hospitalized at an ICU due to drug abuse. - Antunes, Flavia; Oliveira, Magda Lúcia Félix de (Investigación y Educación en Enfermería, 2025)
<!-- [if gte mso 9]> <![endif]--> Objective. To characterize the clinical and demographic profile of patients hospitalized due to drug intoxication at an intensive care unit (ICU) of a teaching hospital between 2004 and 2010. Methodology. In this descriptive study, information was collected from the hospitalized patients, as informed by a Toxicology Care Center (CAT) in Paraná (Brazil). The clinical files were checked and information was collected about age, gender, toxic agents and intoxication circumstances, comorbidities and clinical outcomes. Results: Sixty-two patients were included in the study, with a mean age of 58 years and 77% male. Alcohol was the substance related to most hospitalizations (77%), followed by psychoactive drugs (14%) and marihuana and crack (5% each). The main comorbidities were bronchopneumonia due to aspiration (37%), alcohol-related liver cirrhosis (24%) and traumatic brain injury (19%). The most frequent intoxication circumstances were chronic abuse (79%), attemptive suicide (19%) and acute abuse (4.9%). Thirty-nine percent of the patients died during hospitalization. Conclusion. The results show a concerning reality, as most of the patients are men of economically active age, who were intoxicated by a legal substance like alcohol, with a relevant number of deaths. Nurses need to pay particular attention to this health problem, in the context of which they play a fundamental role as educators with a view to the encouragement of healthy lifestyles. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->